Disaster Risk Reduction of Mangrove Forest Destruction in East Kalimantan Province - Hairun Jariah; Sukindar; Akas Pinaringan Sujalu; Lisa Astria Milasari (Research Advances in Environment, Geography and Earth Science Vol. 9, 2024)
The purpose of this study was to investigate the problems that occur in mangrove forest areas continuously. Such problems have been occurring for a long time, caused by the inaccuracy of previous policies and the overlapping authority and selfishness of stakeholders. A mangrove forest can be briefly defined as a type of forest that grows in tidal areas (especially on sheltered beaches, lagoons, river estuaries) that are inundated at high tide and free from inundation at low tide where the plant community is salt-tolerant. As a result of this research, the implementation of policies carried out by the East Kalimantan Provincial Government can now be said to be successful, although there are still indicators that need to be improved, such as in the resource variable. Furthermore, it was discovered that issues persisted with the previous government’s administration of the Mangrove Forest region. The findings of this study suggest that the policy of private sector activity program be evaluated in conjunction with the Central Government, and that supervision be provided following planting. Provisions in sectoral laws related to natural resources, apart from those that specifically regulate environmental protection as in Law 32/2009, are regulated in various forms. The government’s implementation of policy activity program does not only involve the government and the community, but also involves the private sector and non-governmental organizations (NGOs) as a form of participation in realized forest sustainability and improving the economy of communities in mangrove forest areas.